Down Syndrome–Associated Arthritis Cohort in the New Childhood Arthritis and Rheumatology Research Alliance Registry: Clinical Characteristics, Treatment, and Outcomes. Issue 12 (10th December 2021) - Jones, Jordan T.; Smith, Chelsey; Becker, Mara L.; Lovell, Daniel
Abstract : Objective: Down syndrome–associated arthritis (DA) is underrecognized, and current therapies used for juvenile idiopathic arthritis (JIA) appear to be poorly tolerated and less effective in patients with DA. The objective of this study was to characterize clinical manifestations and therapeutic preferences in DA compared to JIA, using the new Childhood Arthritis and Rheumatology Research Alliance (nCARRA) registry. Methods: In a case–control study, between July 2015 and March 2019, patients with a diagnosis of JIA and Down syndrome (DS) were identified and matched by age, sex, and JIA subtype to patients who have JIA without DS. Collected data included demographic characteristics, disease characteristics, laboratory results, treatment exposure, and outcome measures. Results: A total of 36 children with DA and 165 with JIA were identified. Most patients presented with polyarticular rheumatoid factor–negative disease. At entry into the nCARRA registry, there were minimal differences between the groups, and at the last visit there were significant differences ( P < 0.05) for multiple outcome measures. Patients with DA and those with JIA had similar therapeutic exposure to disease‐modifying antirheumatic drugs (DMARDs) and biologics, but those with DA had more DMARD‐related adverse events (93% versus 25%) and biologic therapy ineffectiveness (60% versus 17%). Conclusion: There was little difference between patients with DA and those with JIA at baseline, and similar therapy was implemented for those in the nCARRA registry; however, at the last visit, the patients with DA had greater disease burden. Additionally, there were more DMARD‐related adverse events and biologic ineffectiveness for those patients with DA. More research is needed to determine differences in pathophysiology and optimal therapeutic approaches.